1998
DOI: 10.1111/j.1467-842x.1998.tb01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Does breastfeeding at six months predict cognitive development?

Abstract: There is controversy over whether the method of feeding in infancy affects intellectual development. We investigated the relationship between breastfeeding status at 6 months of age and long-term

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 24 publications
3
59
2
1
Order By: Relevance
“…These results are consistent with a large body of literature demonstrating advantages of breastfeeding on cognitive function later in life. [28][29][30][31][32][33][34][35][36][37] However, it is important to point out that developmental test scores of all 3 diets groups were within the standardized norms, and differences between BF infants and formula-fed effects were quite small in magnitude and thus difficult to interpret in terms of potential clinical relevance. Previous studies have shown lesser advantages when taking into consideration confounding factors or segregating for variables such as being small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with a large body of literature demonstrating advantages of breastfeeding on cognitive function later in life. [28][29][30][31][32][33][34][35][36][37] However, it is important to point out that developmental test scores of all 3 diets groups were within the standardized norms, and differences between BF infants and formula-fed effects were quite small in magnitude and thus difficult to interpret in terms of potential clinical relevance. Previous studies have shown lesser advantages when taking into consideration confounding factors or segregating for variables such as being small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that factors other than early feeding are more important determinants of cognition. In two separate studies conducted in well-nourished populations, the beneficial effect of breastfeeding on cognitive development in Australian children disappeared after controlling for socio-demographic and environmental factors, including stimulation in the home (Wigg et al, 1998;Zhou et al, 2007). Evidence to date suggests that any advantageous effects of breastfeeding do not seem to be solely attributable to the superior nutrient content of breast milk, and that the beneficial effects of (Simmer, Patole, & Rao, 2008) has failed to show any significant differences in cognitive development between supplemented and unsupplemented formula milk, and there may be other components of breast milk such as enzymes, hormones and growth factors, not present in formula milk, which are more important contributors to cognitive development.…”
Section: Discussionmentioning
confidence: 86%
“…Other research has not found a relationship between breastfeeding and cognition when all confounding factors are accounted for (for example, Der, Batty, & Deary, 2006), and it remains unclear whether differences in cognitive performance reflect a direct nutritional advantage of breast milk, or social and environmental factors that are more favourable in women who breastfeed (Jacobson & Jacobson, 2006). Quality of the home environment has been considered in relatively few studies investigating breastfeeding and cognitive development (Angelson, Vik, Jacobsen, & Bakketeig, 2001;Jacobson, Chiodo, & Jacobson, 1999;Wigg et al, 1998;Zhou, Baghurst, Gibson, & Makrides, 2007). In one study involving a socially disadvantaged population, children aged one and two years who had been breast-fed performed better on the Bayley MDI, after adjusting for home environment (Morrow-Tlucak et al, 1988).…”
Section: Discussionmentioning
confidence: 96%
“…Another metaanalysis showed that only two studies met stringent criteria for inclusion, such as adequate adjustment for socioeconomic status of the family and stimulation of the child (Jain, Concato et al 2002). Of these two studies, one reported a positive association between breastfeeding and intelligence (Johnson, Swank et al 1996), while the other found no benefit (Wigg, Tong et al 1998). …”
Section: Wwwintechopencommentioning
confidence: 99%